Rice research and development in the Flood-Prone Ecosystem (International Rice Research Institute, 2004)
"Rice Research and Development in the Flood-Prone Ecosystem" presents papers and major recommendations from a recent international workshop on Rice Research and Development in the Flood-Prone Rice Lands of South and Southeast Asia.